Generalized Eosinophilia Following Moderna COVID-19 Vaccine Administration: A Case Report. Issue 1 (March 2023) - Hojberg, Yvonne; Abdeljaber, Mahmuod; Prahlow, Joseph A.
Coronavirus disease 19 (COVID-19) vaccination is considered an important part in improving health outcomes globally. While various adverse events following vaccination against COVID-19 have been reported, eosinophilic diseases have rarely been documented in the literature and are poorly understood. Although vaccination is lauded as being "safe, " it has become apparent that adverse reactions related to the vaccines can have detrimental health effects for certain individuals. We present a case of a death related to multiple severe preexisting comorbidities, complicated by new-onset gastrointestinal complaints which were temporally associated with recent COVID-19 vaccination and did not subside, but worsened prior to death. Autopsy revealed evidence of eosinophilic enteritis, associated with ascites, as well as eosinophilic inflammation elsewhere, including the lungs and heart. Histological examination revealed abundant eosinophils in tissues, including the small intestines, epicardium, and lungs. Whether or not the eosinophilic inflammatory process was caused by the recent vaccination cannot be stated with certainty; however, the temporal association between vaccination, symptom onset/progression, and death, and the literature which suggests a possible association between coronavirus vaccination and eosinophilic reactions leads to the conclusion that this death might have been related to an adverse reaction to COVID-19 vaccination.